Integrator is recruited to promoter‐proximally paused RNA Pol II to generate Caenorhabditis elegans piRNA precursors. (19th December 2020) - Beltran, Toni; Pahita, Elena; Ghosh, Subhanita; Lenhard, Boris; Sarkies, Peter
Abstract: Piwi‐interacting RNAs (piRNAs) play key roles in germline development and genome defence in metazoans. In C. elegans, piRNAs are transcribed from > 15, 000 discrete genomic loci by RNA polymerase II (Pol II), resulting in 28 nt short‐capped piRNA precursors. Here, we investigate transcription termination at piRNA loci. We show that the Integrator complex, which terminates snRNA transcription, is recruited to piRNA loci. Moreover, we demonstrate that the catalytic activity of Integrator cleaves nascent capped piRNA precursors associated with promoter‐proximal Pol II, resulting in termination of transcription. Loss of Integrator activity, however, does not result in transcriptional readthrough at the majority of piRNA loci. Taken together, our results draw new parallels between snRNA and piRNA biogenesis in nematodes and provide evidence of a role for the Integrator complex as a terminator of promoter‐proximal RNA polymerase II during piRNA biogenesis. Synopsis: piRNA biogenesis in C. elegans involves transcription of piRNA loci by RNA polymerase II (Pol II) and release of piRNA precursors. Here, the Integrator complex is shown to be recruited to piRNA loci where it cleaves nascent RNA to release short capped piRNA precursors. Integrator localises to sites of piRNA biogenesis in nematodes. Loss of Integrator activity results in reduced piRNA biogenesis. Integrator cleaves nascent RNAs associated with paused RNA polymerase II at piRNA loci to release short capped piRNA precursors from chromatin. Repression of Pol II elongation at the majority of piRNA loci is independent of Integrator. Abstract : Transcription termination and release of short capped piRNA precursors extends the small RNA biogenesis roles of the Integrator complex beyond snRNA.